Sensorless control of matrix converter-fed synchronous reluctance motor drives - Yousefi-Talouki, Arzhang; Stella, Fausto; Odhano, Shafiq; De Lillo, Liliana; Trentin, Andrew; Pellegrino, Gianmario; Zanchetta, Pericle (2017)
This paper presents a sensorless control technique based on direct flux vector control (DFVC) method for synchronous reluctance (SyR) motor drives fed by a three-phase to three-phase matrix converter (MC). Rotor position is estimated based on active flux (AF) concept down to 50 [rpm]. Furthermore, the effect of nonlinear voltage errors of the MC is compensated, and a self-commissioning method capable of identifying the voltage error before compensation is presented and tested. The proposed drive combines the advantages of matrix converters and SyR motors in sensorless fashion, for application into a number of fields, spanning from compact drives for aviation to line-supplied drives for industry applications. Experimental results are provided to prove the feasibility of the proposed technique.